THE MEDIATING ROLE OF CUSTOMER ENGAGEMENT ON THE EFFECT OF USER INTERFACE ON CUSTOMER SATISFACTION ON DIGITAL STREAMING SERVICE USERS - Wisnu Agus Harmawan; Endang Sulistya Rini; Syafrizal Helmi Situmorang (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The development of streaming technology has led to a significant increase in video-on-demand (VOD) services, with competition in Indonesia's SVOD market being intense. The streaming industry faces challenges in managing platforms to satisfy customers and maintain subscriptions. Satisfying customers is a critical goal for streaming service providers, and customer satisfaction is a major result of digital marketing techniques. Customer engagement is one of the factors that affect satisfaction. Besides that, the platform's user interface plays a crucial role in enhancing both customer engagement and satisfaction. However, there is limited research on user interface and customer engagement. This study aims to analyze the effect of user interface on satisfaction through customer engagement using a sample of 260 digital streaming service users in Medan City, consisting of Netflix, Disney+, Prime Video, and HBO GO users. Data analysis techniques using path analysis with approach Structural Equation Modeling (SEM). The results showed that user interface positively and significantly impacts customer engagement and satisfaction. Customer engagement positively and significantly impacts customer satisfaction. Indirectly, user interface positively and significantly impacts customer satisfaction through customer engagement